High-precision local gravity survey along planned motorway tunnel in the Slovak Karst - ZAHOREC, Pavol; PAPČO, Juraj; VAJDA, Peter; SZABÓ, Stanislav (Contributions to Geophysics and Geodesy, 2019)
Results from a detailed gravity survey realized along the planned highway tunnel in the karstic area of Slovak Karst in the eastern Slovakia are presented. Detailed gravity profiles crossed an area of rugged topography, therefore the terrain corrections played a crucial role in the gravity data processing. The airborne laser scanning technique (LiDAR) was used in order to compile a high-resolution digital terrain model (DTM) of the surrounding area and to calculate terrain corrections properly. The difference between the Bouguer anomalies calculated with an available nationwide DTM and those with new LiDAR-based model can be significant in some places as it is presented in the paper. A new method for Bouguer correction density analysis based on surface data is presented. Special underground gravity measurements in the existing nearby railway tunnel were also conducted in order to determine the mean density of the topographic rocks. The Bouguer anomalies were used to interpret lithological contacts and tectonic/karstic discontinuities.